Computational Conjugate Heat Transfer Analysis of a Hybrid Electric Vehicle Inverter. Issue 19 (26th November 2018) - Yang, Yang; Liou, William; Kang, Xiaosong
ABSTRACT: A physics-based computational simulation of the heat transfer characteristics of an insulated gate bipolar transistor (IGBT) developmental inverter is reported. The simulation considers the fluid/thermal multiphysics interactions via a conjugate heat transfer analysis. The fluid phase includes air and liquid coolant; the solid phase, where the heat is conducted, includes various solid materials. Numerical solutions of the heat conduction and convection phenomena in and around the IGBT modules and the inverter, built as a three-dimensional computational model, are sought for by using parallel computing. Comparisons with the available experimental data show a satisfactory agreement of the inverter temperature at three power levels under two different coolant flow rates. Detailed examination of the flow field reveals that the design features of the rectangular coolant flow chamber in the heat sink and the small clearance between the tips of the pin fin and the walls lead to an evenly distributed coolant flow around most of the pin fins. The temperature distributions of the pin fins depend highly on their locations relative to the IGBT modules. The findings from the current study can be useful in future efforts to optimize the thermal performance of IGBT inverters.